Complex host genetic susceptibility to Staphylococcus aureus infections. Issue 9 (September 2015) - Shukla, Sanjay K.; Rose, Warren; Schrodi, Steven J.
Highlights Great care is needed to select cases and controls for genetic studies of Staphylococcus aureus infection. Infection susceptibility involves cell adhesion, invasion, and innate and adaptive immunity. Genetics of S. aureus carriage and severe infection involves different host factors. Susceptibility to S. aureus infections is polygenic due to pathogen versatility. S. aureus infection severity, trajectory, and tissue specificity are polygenic.